2013
DOI: 10.1080/09593330.2013.808244
|View full text |Cite
|
Sign up to set email alerts
|

The application of microfiltration-reverse osmosis/nanofiltration to trace organics removal for municipal wastewater reuse

Abstract: The fate of organic micropollutans (MPs) in a membrane system based on microfiltration (MF) and reverse osmosis/nanofiltration (RO/NF) has been investigated for the case of wastewater reuse. Both an operating full-scale water reuse plant and a pilot plant were employed, with 22 individual organic compounds at their ambient concentrations studied for the former and the latter employing two target compounds over a range of feed concentrations. Results revealed removal efficiencies higher than 75% for most compou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(19 citation statements)
references
References 20 publications
1
17
0
1
Order By: Relevance
“…The substances with the highest concentrations in the inflow were salicylic acid, ibuprofen and bisphenol-A (6.3 - Garcia et al [28] assessed the removal of 20 micropollutants at a WTS equipped with tertiary treatment with MF and RO membranes in sequence, finding that only ibuprofen and nonylphenol were not efficiently removed (<30%), in contrast to the other substances (>75%). Therefore, they decided to study the removal of the two former substances in a pilot plant having a membrane bioreactor (MBR) system followed by a MSP system, alternating with NF and RO membranes.…”
Section: Membrane Separation Processmentioning
confidence: 99%
“…The substances with the highest concentrations in the inflow were salicylic acid, ibuprofen and bisphenol-A (6.3 - Garcia et al [28] assessed the removal of 20 micropollutants at a WTS equipped with tertiary treatment with MF and RO membranes in sequence, finding that only ibuprofen and nonylphenol were not efficiently removed (<30%), in contrast to the other substances (>75%). Therefore, they decided to study the removal of the two former substances in a pilot plant having a membrane bioreactor (MBR) system followed by a MSP system, alternating with NF and RO membranes.…”
Section: Membrane Separation Processmentioning
confidence: 99%
“…However, different comparative works [22,39,43,71] concluded that, although the retention of microcontaminants by NF is lower than that obtained by RO, the latter has demonstrated only marginally increased rejection in comparison with NF.…”
Section: Membrane Filtrationmentioning
confidence: 84%
“…The authors suggested RO as the final step in a water reuse application, where removal of microcontaminants is of particular concern. Garcia et al [43] studied the efficiency in the removal of 22 "priority" microcontaminants in a municipal WWTP for water reuse using MF and RO. Although MF was able to remove some compounds by more than 50%, the incorporation of RO significantly enhanced the removal efficiency, ranging from 65% to 90% for most microcontaminants other than naphthalene and ibuprofen.…”
Section: Nanofiltration and Reverse Osmosismentioning
confidence: 99%
“…Therefore, these processes should be combined with other treatment methods such as nanofiltration (NF) or reverse osmosis (RO). Garcia et al (2013) combined the MF and RO processes in order to remove micropollutants for reuse of domestic wastewater. For example, DEHP was removed up to 50 % with only microfiltration treatment.…”
Section: Membrane Processesmentioning
confidence: 99%